Situation Report: Hungary, 18 January 1972 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Prices and the Public Hungary's 1972 Budget: Key Figures Hungary Studies the Financial Consequences of Protracted Investments Comecon Investment Bank Loan for Hungarian Railways Economic Co-operation with the West: Prospects and Problems Western Films in Hungary Nazi Indemnities in Hungary Agricultural Co-operatives Battle State Construction Monopoly Thermal Waters and Western Know-How Help Vegetable Production Party Encroachments on Self-government in the Agricultural Producers' Co-Operatives